FEMALE TRAFFICKING: STRATEGY IN PREVENTION - Grace Jenny Soputan, Ferdinand Kerebungu , Elni J Usoh (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The purpose of this research is to construct a model of female trafficking prevention basing upon economic empowerment. The study focused on strategy in prevention. The method used is Participatory Action Research. Quantitative data were collected by distributing questionnaires to 250 participants about community knowledge of trafficking. Qualitative data were obtained by interviewing to a male traffickers, 2 government officials, 5 community members, and 1 victim. This study applies percentage analysis to know about quantitatively about knowlegde trafficking while qualitative approach is intended to demonstrate how to prevent female trafficking. They had lack of knowledge on human trafficking. The researcher designed the strategy to prevent women trafficking and how to implement for primary and secondary methods by government and community. To reduce trafficking, cooperation between the government and the community is needed to deal with this issue.